MENGGALI POLA ASUH ORANG TUA BAGI KESUKSESAN MASA DEPAN ANAK AUTISME: STUDI LITERATUR - Begum, Sayyidah Amatul (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Parenting for every child does need the best, because there will be readiness in him related to several abilities that will affect in the future, such as cognitive, behavioral, and emotional abilities. This is not only given to individuals who are outwardly perfect, but individuals who have underdevelopment also need good parenting, one of which is the underdeveloped group, namely children with autism. The importance of this is to silence the negative views of the community and the attitude of parents to deny children with autism. Ideally, families and the community provide support to parents who have children with autism, as a form of self-reinforcement in providing good parenting. The research method used is a qualitative approach, with data collection techniques involving literature searches using scientific search engines and related organization websites. Data analysis is carried out through qualitative content analysis, which includes the identification of themes and subthemes, analysis of the relationship between them, and drawing conclusions about the research topic. The results of this study are known that the role of parents in providing good parenting and especially for their children with autism is very important in supporting success in the future. Moreover, it is also supported by the deployment of parents to their children to do therapy regularly, so that as parents will get information related to things that can be applied as a form of support and encouragement for their children in developing their abilities. Thus, parents are one of the most important leaders in providing good parenting for children, in order to achieve hope and success in the future, especially in the autism group.